Grain sorghum production: Influence of planting date, hybrid selection, and insecticide application. Issue 2 (19th May 2021) - Zander, Anna; Lofton, Josh; Harris, Chase; Kezar, Sarah
Abstract: Grain sorghum [ Sorghum bicolor (L.) Moench] has been a valuable crop for the southern Great Plains due to its ability to overcome the high temperatures and sporadic rain events common in the region. Optimizing production practices has always been critical for grain sorghum to overcome these environmental challenges. In response to sugarcane aphids (SCA), a detrimental pest in grain sorghum production, common agronomic management practices rapidly shifted with no regard to how such changes would affect overall production. This research is aimed to evaluate the effects of the hasty management changes on grain sorghum plant stands and yields in Oklahoma. Trials were established in 2016 and 2017 at the Northcentral Research Station in Lahoma, OK, and the Efaw Research Station near Stillwater, OK. Four planting dates, two hybrid types, and insecticide applications were evaluated on their impact on early‐season stands and crop yield. Findings showed that planting date had the most consistent impact on sorghum yields, across hybrid types and insecticide applications. Planting in April resulted in higher yields in 2016. However, results from 2017 showed that cooler soil temperatures, as measured by Mesonet stations at each location, can still limit yield when grain sorghum is planted too early. Early‐season plant stands followed the same trend as crop yields, with the highest early‐season stands occurring in the same period as highest yields. Yields and stands consistently decreased with later planting. It was also during these later planting dates that hybrid selection and insecticide applications were found to have a significant impact on yield.